Public‐private‐people partnership as a way to reduce carbon dioxide emissions from residential development - Kuronen, Matti; Junnila, Seppo; Majamaa, Wisa; Niiranen, Ilkka (International Journal of Strategic Property Management, 2010)
This paper examines the possibility of Public‐Private‐People partnership (4P) model as a way to reduce carbon dioxide emissions from residential developments. The case project focuses on the energy system design as a part of urban planning. Based on the case experiences, the paper presents a 4P framework for low‐carbon residential development systems. The theoretical model was tested in one specific case project, Nupurinkartano. The major findings were that the 4P framework is a relevant tool for decreasing carbon emissions when planning a new development; the applied solution delivered an energy system design that could reduce the CO2 emissions of the development by 75%. Based on literature this paper suggests that a new development should be viewed as one system instead of several different subsystems. The paper concludes by suggesting that 4P offers an alternative approach for urban planning, specifically energy system planning, and it can deliver significant improvements in carbon efficiency.First Published Online: 09 Jun 2011